Growth and decay of acceleration waves in non-ideal gas flow with radiative heat transfer - Singh L.P.; Singh R.; Ram S. (My University, 2025)
The present paper is concerned with the study of the propagation of acceleration waves along the characteristic path in a non-ideal gas flow with effect of radiative heat transfer. It is shown that a linear solution in the characteristic plane can exhibit non-linear behavior in the physical plane. It is also investigated as to how the radiative heat transfer under the optically thin limit will affect the formation of shock in planer, cylindrical and spherically symmetric flows. We conclude that there exists critical amplitude such that any compressive waves with initial amplitude greater than the critical one terminate into shock waves while an initial amplitude less than the critical one results in the decay of the disturbance. The critical time for shock formation has been computed. In this paper we also compare/contrast the nature of solution in ideal and non ideal gas flows. © Versita sp. z o.o.